2017
DOI: 10.3892/etm.2017.5171
|View full text |Cite
|
Sign up to set email alerts
|

Contrast‑enhanced ultrasound is better than magnetic resonance imaging in evaluating the short‑term results of microwave ablation treatment of uterine fibroids

Abstract: Abstract. Contrast-enhanced ultrasound (CEUS) and magnetic resonance imaging (MRI) were compared in evaluating the short-term effects of microwave ablation (MWA) on uterine fibroids. A total of 60 patients with uterine fibroids treated by MWA were enrolled in the experimental group during their two-year follow-up period according to the inclusion criteria. Conventional two-dimensional US, MRI and CEUS were performed to determine the volume reduction and the fibroid residue by displaying the size, echo and sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 13 publications
(14 reference statements)
0
5
0
Order By: Relevance
“…[ 1 ] The common symptoms of UFs are abnormal menstrual bleeding, urinary or pelvic discomfort, dysmenorrhea, dyspareunia, infertility, and repeated miscarriages, seriously affecting the quality of patients’ life. [ 1 , 2 ] At present, comprehensive application of traditional surgery (myomectomy or hysterectomy), drug treatment, [ 3 ] radiofrequency ablation, [ 4 , 5 ] microwave ablation, [ 6 , 7 ] and uterine artery embolization [ 8 10 ] greatly improves the treatment outcome of UFs. Even so, these methods have some traumatic and limitations, including the risk of infection, postembolization syndrome and permanent amenorrhea.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 ] The common symptoms of UFs are abnormal menstrual bleeding, urinary or pelvic discomfort, dysmenorrhea, dyspareunia, infertility, and repeated miscarriages, seriously affecting the quality of patients’ life. [ 1 , 2 ] At present, comprehensive application of traditional surgery (myomectomy or hysterectomy), drug treatment, [ 3 ] radiofrequency ablation, [ 4 , 5 ] microwave ablation, [ 6 , 7 ] and uterine artery embolization [ 8 10 ] greatly improves the treatment outcome of UFs. Even so, these methods have some traumatic and limitations, including the risk of infection, postembolization syndrome and permanent amenorrhea.…”
Section: Introductionmentioning
confidence: 99%
“…Where HIFU works within diagnostic frequencies (0.6–5.0 MHz), microwave ablation works with electromagnetic waves (900–2450 MHz) and is typically used to ablate larger tumors (>3.0 cm). 57 Four studies demonstrated the use of CEUS for monitoring microwave ablation of fibroids, 31,33,36,38 and two studies for monitoring this treatment of adenomyosis. 37,40 Quantitative analysis demonstrated good agreement between contrast-enhanced MRI and CEUS for detecting non-perfused volume after microwave ablation of fibroids (ICC = 0.991) 33 and ablation rate in adenomyosis ( R = 0.81).…”
Section: Resultsmentioning
confidence: 99%
“…Remarkably, none of the studies that used CEUS as a diagnostic tool performed an MRI, all used histology as reference test. Fifteen studies performed MRI as post-treatment imaging modality, of which six studies described that results obtained with both CEUS and MRI were similar [27][28][29]38,41,45 and four studies made a statistical comparison of CEUS with MRI 33,35,40,47 in gynecology. In the characterization of nongynecology malignancies, for example focal hepatic lesions and recognizing malignancies, there are studies showing a similar-to-higher accuracy of CEUS compared with MRI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contrast-enhanced ultrasound (CEUS) is a promising non-invasive technique that can more intuitively and efficiently reveal the blood supply or perfusion characteristics of tumors. CEUS has been widely used to distinguish between benign and malignant lesions in the breast, thyroid, liver, and other organs, and it has also been used to monitor tumor response after neoadjuvant chemotherapy and to evaluate the effect of radiofrequency or microwave ablation (6)(7)(8)(9)(10)(11). However, there was no report on the assessment of laryngeal cancer by CEUS.…”
Section: Introductionmentioning
confidence: 99%